Cynthia Tompkins. Experimental Latin American Cinema. Austin: U of Texas P, 2013. x+ 294 pp. - Carolina Rocha (Studies in 20th & 21st Century Literature, 2014)
Review of Cynthia Tompkins. Experimental Latin American Cinema. Austin: U of Texas P, 2013. x+ 294 pp.
Keywords: Latin America; film; cinema